Verdwenen Aarde : Kunstproject in de St.-Bernardusabdij te Hemiksem. - Meyvis, Zjos; Coenjaerts, Raf (Hemiksem : De Verdwenen Aarde vzw, 1988)
Annaert, Gunter ; Arnauts, Guido ; Bauwens, Peter ; Bellemans, Corry ; Bello ; Boelen, Legs ; Boffin, Fred ; Bracke, Jo ; Brusselairs, Din ; Clicque, Robert ; Debie, Annie ; Defevere, Henk ; De Ranter, Jules ; De Schrijver, Hendrik ; Fabre, Friedel ; Green, Bryan ; Hulstaert, Frederik ; etc.
Verdwenen Aarde : Kunstproject in de St.-Bernardusabdij te Hemiksem, 15 juli 1988 - 28 augustus 1988
kunstcatalogus